Pre-Project Selling of Apartment Developments: Reconstructing Project Completion Guarantees as a Form of Consumer Legal Protection in Condominium Housing - Muhammad Zaki Mubarrak; Gusti Rian Saputra (Istinbath : Jurnal Hukum, 2025)
The practice of marketing apartment projects through pre-project selling schemes has become the dominant model for vertical housing development in Indonesia. Although formally legitimized by positive law, this practice carries structural risks, particularly project incompletion, which directly harms consumer interests. Existing legal protection is still contractual in nature through the Sale and Purchase Agreement (PPJB) and relies on dispute resolution mechanisms after a default. Consequently, consumer protection is reactive and has not been able to guarantee the actual completion of housing projects. This study aims to examine the weaknesses of consumer protection in the pre-project selling scheme for apartment construction in Indonesia and to formulate the concept of project completion guarantees as a form of preventive legal protection. This study uses a normative legal research method with regulatory, conceptual, and comparative approaches. The analysis focuses on Law Number 20 of 2011 concerning Flats, applicable contractual practices, and a comparative study of countries that have implemented escrow account mechanisms, financial guarantees, and public supervision in pre-construction housing transactions. The study results show that the absence of a project completion guarantee obligation leads to an unfair transfer of construction risk from developers to consumers. Therefore, this study proposes the reconstruction of the legal framework for apartment buildings in Indonesia through the institutionalization of a project completion guarantee based on a combination of guaranteed fund management and public supervision as part of Ius Constituendum. This approach is expected to strengthen consumer protection, increase legal certainty, and encourage the fair and sustainable governance of vertical housing developments. [Praktik pemasaran proyek apartemen melalui skema pre-project selling telah menjadi model yang dominan dalam pengembangan perumahan vertikal di Indonesia. Meskipun secara formal telah dilegitimasi oleh hukum positif, praktik ini mengandung risiko struktural, khususnya ketidakselesaian proyek, yang secara langsung merugikan konsumen. Perlindungan hukum yang ada saat ini masih bersifat kontraktual melalui Perjanjian Pengikatan Jual Beli (PPJB) dan bertumpu pada mekanisme penyelesaian sengketa setelah terjadinya wanprestasi. Akibatnya, perlindungan konsumen bersifat reaktif dan belum mampu menjamin terealisasinya penyelesaian proyek perumahan secara nyata. Penelitian ini bertujuan untuk mengkaji kelemahan perlindungan konsumen dalam skema pre-project selling pada pembangunan apartemen di Indonesia serta merumuskan konsep jaminan penyelesaian proyek sebagai bentuk perlindungan hukum preventif. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan peraturan perundang-undangan, konseptual, dan perbandingan hukum. Analisis difokuskan pada Undang-Undang Nomor 20 Tahun 2011 tentang Rumah Susun, praktik kontraktual yang berlaku, serta kajian perbandingan dari negara-negara yang telah menerapkan mekanisme rekening escrow, jaminan keuangan, dan pengawasan publik dalam transaksi perumahan pra-konstruksi. Hasil penelitian menunjukkan bahwa ketiadaan kewajiban jaminan penyelesaian proyek telah menyebabkan terjadinya pengalihan risiko pembangunan secara tidak adil dari pengembang kepada konsumen. Oleh karena itu, penelitian ini mengusulkan rekonstruksi kerangka hukum rumah susun di Indonesia melalui pelembagaan jaminan penyelesaian proyek yang berbasis pada kombinasi pengelolaan dana yang terjamin dan pengawasan publik sebagai bagian dari ius constituendum. Pendekatan ini diharapkan mampu memperkuat perlindungan konsumen, meningkatkan kepastian hukum, serta mendorong tata kelola pembangunan perumahan vertikal yang adil dan berkelanjutan.]